Perencanaan lanskap daya tarik wisata sejarah eks Pelabuhan Buleleng - Wibawa, Kadek Agus Arya; Yusiana, Lury Sevita; Sudana, I Putu (Jurnal Arsitektur Lansekap, 2020)
The city of Singaraja was once the capital city of Soenda Ketjil until 1958. Several supporting infrastructures for the capital city were built, one of which was a port called Pelabuhan Buleleng which was the main port to the Province of Bali. The transfer of the capital and the main port of Bali Province became the beginning of the decline of the function of the Port of Buleleng so that it needs to be carried out planning the landscape of the historical tourism attraction of the Ex-Port of Buleleng. The purpose of this study was to analyze the site related to the potential and constraints in tourism development and determine appropriate planning in the effort to arrange the Ex-Buleleng Port as a historical tourist attraction in Singaraja City. The method used is the survey method. The stages of this research are preparation of inventory, analysis, synthesis, and design. The method of data collection is done through field observations, interviews with speakers, literature studies, and distributing questionnaires (communities and visitors). The results of this study show the potential of historical value on the site that can be used as a historical tourist attraction, while the problems encountered include problems of circulation, cleanliness, structuring, and other supporting facilities. The planning concept produced in this study is educative and recreational historical tourism that is able to support the preservation of historical resources on the site by making the Ex-Buleleng Port as a historical and cultural information center and recreation in the Buleleng Regency. Suggestions that can be given are recommendations on the concept of tourist space, accessibility and circulation, tourist facilities, the concept of vegetation and tourism activities